Preclinical evaluation of OMVs as potential vaccine candidates against Salmonella enterica serovar Enteritidis infection - Jiang, Xi; Chu, Chao; Wang, Zhenyu; Gu, Jiaojie; Hong, Yaming; Li, Qiuchun; Jiao, Xinan (Frontiers in Cellular and Infection Microbiology, 2022)
Salmonella enterica serovar Enteritidis is the most prevalent serotype that causes human infections worldwide. Consumption of S. Enteritidis-contaminated animal foods is a major source of human infections; however, eradicating bacteria from animals remains difficult. Therefore, it is necessary to develop new measures to prevent and control salmonellosis. Here, we used the outer-membrane vesicles (OMVs) of S. Enteritidis and assessed their protective efficacy and immune response in mice. Deletion of tolR in S. Enteritidis increased the production and size of OMVs compared to those in the wild type (WT) and ΔrfaQ strains. Intramuscular immunization with OMVs conferred greater protection than intraperitoneal and intranasal immunization. Moreover, OMVs extracted from both WT and ΔtolR strains provided an 83.3% protective rate in mice challenged with S. Enteritidis, which was higher than that provided by OMVs extracted from the ΔrfaQ strain. However, compared with OMVs from the ΔtolR strain, OMVs from WT and ΔrfaQ strains rapidly eradicated S. Enteritidis colonizing the liver, spleen, ileum, and cecum of BALB/c mice after immunization. Immunization with OMVs from each of the three strains induced humoral immune responses and showed no side effects on the growth of mice. Our study revealed that OMVs from various S. Enteritidis strains could be developed for use as subunit vaccine candidates against nontyphoidal Salmonella infections in mammals.